The Conundrum of Antidepressant-Induced Anhedonia: A Blended Patient–Psychologist Perspective - Nicholas Norman Adams MA(Hons), MSc, PhD, CPsychol, RSci, AFBPsS (Journal of Patient Experience)
This article constitutes a Patient Perspective, grounded in lived experience, its primary aim is to enhance awareness of antidepressant-induced anhedonia by providing experience-based insights, relevant to clinicians, researchers, and caregivers. My own experiences with treatment-resistant depression-anxiety have been significant and long-lasting. In my 22-year-plus journey of illness experience—and having taken over 23 antidepressant medications—emotional-blunting, anhedonia, and mania have all, at times, been side-effect-related factors. This work explores the conundrum of antidepressant-induced anhedonia, developing an in-depth patient perspective useful for mental health practitioners, psychiatrists, psychologists, and for wider formal professional and informal nonprofessional caring actors. I write this via a reflexive lens as a long-term mental health patient, while also recognizing my dual-positionality as a Chartered Psychologist and an academic with a PhD working in the field of mental health. Thus, my dual-perspective provides a unique lens useful for translating the patient experience to a wider caregiving audience: fostering understanding and deepened awareness of the anhedonia experience. Implications for patient care are discussed.